Alcances de la aplicación del criterio de extensión geográfica del uso por el Indecopi en la resolución de conflictos entre registro de marca y uso del nombre comercial - Rentería Carrera, Johaan Alejandro (2019)
ABSTRACT This research aims to address a proper subject of Industrial Property Law, as is the Tradename and must be noted that the scope of protection is not regulated in national or supranational legislation, persisting a conflict between the use of this sign and the registration of a trademark. So, this study will determine how the exclusive right to the trademark is affected by the application of a criterion, that determine the protection of the tradename, but without regulatory support. In addition, this research has two chapters, the first one is about the content of the tradename, both in doctrine and case law, and the second one is about the exclusive rights to the tradename. Also, this project has the analysis of the Resolutions issued by the Board of Intellectual Property and the Resolutions issued by the Court of Justice of the Andean Community; counting also with the commentaries from two specialists in Intellectual Property, to clarify even further the scope of the Tradename